중력모형을 통한 거시경제와 한국 항공화물 수출입 관계 연구 - 박상용; Sang-Yong Park (한국항공운항학회지, 2024)
This study analyzed the importance of Korean air cargo transport in the increasingly close international trade and logistics network due to the acceleration of globalization and digitalization. Korea serves as an East Asian logistics hub centered on Incheon International Airport, and contributes significantly to economic growth and international trade through air cargo transport. The study analyzed air cargo exports and imports between Korea and major trading partners (the United States, China, Vietnam, and Japan) from 2003 to 2023 using a gravity model. The results of the analysis showed that GDP per capita and population of the counterpart country acted as factors that increased export volume, and fluctuations in international oil prices and the number of airports in the counterpart country also had a significant impact on exports. On the other hand, Korea's GDP per capita and exchange rate fluctuations had a negative impact on export volume. In terms of import volume, Korea's GDP per capita and transportation infrastructure of the counterpart country had a positive impact, while flight distance had a negative impact. These results will provide useful implications for establishing Korea's air cargo transport policy and trade strategy.